2013
DOI: 10.1002/micr.22109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between suture and fibrin glue on repair by direct coaptation or tubulization of injured mouse sciatic nerve

Abstract: These results suggest that the use of fibrin glue in nerve repair by either direct coaptation or tubulization is an alternative to conventional suture repair, particularly in case of small-size-nerve reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 56 publications
2
30
0
4
Order By: Relevance
“…An important parameter confirming the functional improvement in our study was the g-ratio, which has been described as an index that reflects the optimal axonal myelination that leads to an appropriate conduction of action potentials (9). The g-ratio can simply be denoted as the ratio of axon circumference to myelin circumference, and this value will always be less than 1; however, remyelinated axons tend to have values closer to 1 than naturally myelinated axons.…”
Section: █ Discussionsupporting
confidence: 58%
“…An important parameter confirming the functional improvement in our study was the g-ratio, which has been described as an index that reflects the optimal axonal myelination that leads to an appropriate conduction of action potentials (9). The g-ratio can simply be denoted as the ratio of axon circumference to myelin circumference, and this value will always be less than 1; however, remyelinated axons tend to have values closer to 1 than naturally myelinated axons.…”
Section: █ Discussionsupporting
confidence: 58%
“…In sectioned nerves, the first option of repair is the end-to-end neurorraphy, joining the stumps through suture or through adhesives (e.g fibrin glue) 7,16 . In some cases, according to the extension of the lesion, it is not possible unite the stumps and suture them without causing tension to the nerve, fact that occurs mainly when this rupture involves the loss of tissue.…”
Section: ■ Discussionmentioning
confidence: 99%
“…and not presenting autologous nerve graft morbidity in donor nerve removal, being able to regenerate the Sciatic nerve and thus the structures innervated 7,8 . This advantage was also reported by Demir et al 18 , who compared the use of the vein to that of a synthetic collagen tube in a 10 mm gap, and concluded that both, Tube of synthetic collagen and autologous vein grafts, produced similar results, however, with vein grafting being slightly more effective.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations